Geographical analysis of evaluated chronic disease programs for Aboriginal and Torres Strait Islander people in the Australian primary health care setting: a systematic scoping review - Hannah Beks; Marley J. Binder; Constance Kourbelis; Geraldine Ewing; James Charles; Yin Paradies; Robyn A. Clark; Vincent L. Versace (BMC, 2019)
Abstract Background Targeted chronic disease programs are vital to improving health outcomes for Indigenous people globally. In Australia it is not known where evaluated chronic disease programs for Aboriginal and Torres Strait Islander people have been implemented. This scoping review geographically examines where evaluated chronic disease programs for Aboriginal people have been implemented in the Australian primary health care setting. Secondary objectives include scoping programs for evidence of partnerships with Aboriginal organisations, and use of ethical protocols. By doing so, geographical gaps in the literature and variations in ethical approaches to conducting program evaluations are highlighted. Methods The objectives, inclusion criteria and methods for this scoping review were specified in advance and documented in a published protocol. This scoping review was undertaken in accordance with the Joanna Briggs Institute (JBI) scoping review methodology. The search included 11 academic databases, clinical trial registries, and the grey literature. Results The search resulted in 6894 citations, with 241 retrieved from the grey literature and targeted organisation websites. Title, abstract, and full-text screening was conducted by two independent reviewers, with 314 citations undergoing full review. Of these, 74 citations evaluating 50 programs met the inclusion criteria. Of the programs included in the geographical analysis (n = 40), 32.1% were implemented in Major Cities and 29.6% in Very Remote areas of Australia. A smaller proportion of programs were delivered in Inner Regional (12.3%), Outer Regional (18.5%) and Remote areas (7.4%) of Australia. Overall, 90% (n = 45) of the included programs collaborated with an Aboriginal organisation in the implementation and/or evaluation of the program. Variation in the use of ethical guidelines and protocols in the evaluation process was evident. Conclusions A greater focus on the evaluation of chronic disease programs for Aboriginal people residing in Inner and Outer Regional areas, and Remote areas of Australia is required. Across all geographical areas further efforts should be made to conduct evaluations in partnership with Aboriginal communities residing in the geographical region of program implementation. The need for more scientifically and ethically rigorous approaches to Aboriginal health program evaluations is evident.